A bendable electromagnetic shielding film and preparation method thereof
By using the structural design of PET-type matte release carrier film, the first insulating layer of epoxy resin, the second insulating layer of polyurethane resin, the ultra-thin copper foil shielding layer, the adhesive layer and the PET release protective film in the electromagnetic shielding film, the existing electromagnetic shielding film is solved, and the high shielding efficiency and bending resistance are improved, meeting the high performance requirements of 5G communication equipment.
Patent Information
- Application Number
- CN201911173241.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-11-26
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2039-11-26
AI Technical Summary
The existing electromagnetic shielding film is not resistant to solvent wipe and reflow soldering in communication electronic equipment, and it is difficult to meet the high shielding efficiency requirements of 5G communication equipment.
The bendable electromagnetic shielding film structure is adopted, including a PET-type matte release carrier film, an epoxy resin first insulating layer, a polyurethane resin second insulating layer, an ultra-thin copper foil shielding layer, an adhesive layer and a PET release protective film. By optimizing the thickness and material formula of each layer, the film's solvent wiping and reflow soldering performance is improved.
It realizes the high shielding performance of the electromagnetic shielding film, can withstand 288℃10s×3 soldering times, and can be bent for a certain number of times, meeting the high performance requirements of 5G communication equipment.
Smart Images

Figure CN110839339B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electromagnetic shielding, and in particular relates to an electromagnetic shielding film that can be bent for use and a preparation method thereof. Background Art
[0002] Electromagnetic shielding film is a new type of electromagnetic shielding material that can block the penetration of electromagnetic waves, prevent electromagnetic radiation, protect electronic information from leakage and resist electromagnetic interference. It can effectively prevent electromagnetic waves from harming the human body, and shield electromagnetic radiation from interfering with electronic equipment to ensure the normal operation of the equipment. At the same time, by blocking the transmission of electromagnetic signals, it can also ensure that electronic information is not leaked or stolen.
[0003] Flexible Printed Circuit Board (FPC) is a connecting line in electronic devices, mainly for conducting current and transmitting signals. When the signal transmission line is distributed on the outermost layer of FPC, in order to avoid signal distortion caused by electromagnetic interference during signal transmission, FPC is laminated with a layer of electromagnetic shielding film after laminating the cover film to shield the electromagnetic interference from outside.
[0004] With the advent of the high-frequency and high-speed 5G era and the development of wearable devices, higher requirements are placed on electromagnetic shielding film materials. The electromagnetic shielding film shielding layer currently used in electronic information equipment is mainly metal plating, mainly including copper plating, silver plating, nickel plating, etc. However, the shielding effectiveness of electromagnetic shielding films using metal plating as the shielding layer is usually around 60dB, which is difficult to meet the shielding effectiveness requirement of 5G communication electronic equipment of more than 80dB.
[0005] In order to improve the shielding effectiveness of the electromagnetic shielding film, the number of shielding layers can be increased to obtain an electromagnetic shielding film with two or more shielding layers. Chinese invention patent application CN102711428A (A very thin shielding film with high shielding effectiveness and its manufacturing method) provides an extremely thin shielding film with high shielding effectiveness, including more than two solid shielding layers. The shielding film can reflect and absorb high-frequency interference signals multiple times, and at the same time introduce excess charge into the ground layer to achieve high shielding effectiveness. However, after using this technology, the shielding effectiveness of the shielding film is still only more than 60dB. Chinese invention patent application CN104853576A (Electromagnetic shielding film with ultra-high shielding performance and its production process) provides an electromagnetic shielding film with ultra-high shielding effectiveness, including a carrier layer, an insulating layer, a first metal layer, a first adhesive layer, a second metal layer, a second conductive adhesive layer and a protective layer arranged once, wherein the first metal layer is an electroplated metal layer, and the second metal layer is filled in the mesh pores of the first adhesive layer. The electromagnetic shielding value of the electromagnetic shielding film provided by this technology can reach more than 75dB, but still cannot exceed 80dB.
[0006] Another way to improve shielding effectiveness is to use ultra-thin metal foil. Ultra-thin metal foil has higher conductivity and is thicker than the spot-plated metal layer, so it can achieve very high shielding effectiveness. However, for electromagnetic shielding film, there may be the following problems when using it in communication electronic equipment: 1. The FPC in communication electronic equipment needs to be cleaned with solvents during the manufacturing process, so the various materials in the electromagnetic shielding film are required to have good solvent wiping resistance, while the adhesive layer in the prior art has poor solvent wiping resistance; 2. When pressing (conditions such as 180°C, 10MPa, 2min) the FPC, it is easy to be broken at the edge of the copper wire (at the step difference), thereby leaking the metal shielding layer. 3. When the electromagnetic shielding film is used in communication electronic equipment, reflow soldering is required, so the electromagnetic shielding film is also required to have high reflow soldering performance, while the matrix resin in the prior art is a thermoplastic resin, which is not resistant to reflow soldering. Summary of the invention
[0007] The technical problem to be solved by the present invention is that the electromagnetic shielding film in the prior art is not resistant to solvent wiping and reflow soldering when used in communication electronic equipment.
[0008] In order to solve the above technical problems, the present invention discloses a bendable electromagnetic shielding film and a preparation method thereof, wherein the bendable electromagnetic shielding film comprises a release carrier film, a first insulating layer coated on the release carrier film, a second insulating layer coated on the first insulating layer, a metal foil shielding layer attached to the second insulating layer, an adhesive layer provided on the metal foil shielding layer, and a release protective film attached to the adhesive layer;
[0009] The thickness of the release carrier film is 25-125 μm, the thickness of the first insulating layer is 2-5 μm, the thickness of the second insulating layer is 3-10 μm, the thickness of the metal foil shielding layer is 2-8 μm, the thickness of the adhesive layer is 5-15 μm, and the thickness of the release protective film is 30-80 μm.
[0010] Among them, the release carrier film is a PET type matte release film; the metal foil shielding layer is an ultra-thin metal foil layer, specifically an electrolytic copper foil or a rolled copper foil, with a thickness of 2-8 μm; and the release protective film is a PET release film or a micro-adhesive film.
[0011] The first insulating layer is epoxy resin, which is obtained by chemical reaction of epoxy resin prepolymer, curing agent, pigment and additive A; in parts by mass, the epoxy resin prepolymer is 30-65 parts, the curing agent is 15-35 parts, the pigment is 5-15 parts, and the additive A is 5-25 parts. The first insulating layer is black and has a thickness of 2-5 μm, wherein the epoxy resin prepolymer includes but is not limited to one or a mixture of bisphenol A epoxy resin prepolymer, bisphenol F epoxy resin prepolymer, phenolic epoxy resin prepolymer, bisphenol S epoxy resin prepolymer, hydantoin epoxy resin prepolymer, bisphenol fluorene epoxy resin prepolymer, biphenyl epoxy resin prepolymer, and alicyclic epoxy resin prepolymer. The curing agent includes one or more of aromatic amines (p-diaminodiphenyl sulfone, p-diaminodiphenylmethane, m-phenylenediamine), alicyclic amines (isophorone diamine, 1,2-cyclohexanediamine, hydrogenated p-diaminodiphenylmethane), phenolic aldehydes (phenol type, o-cresol formaldehyde type, bisphenol A formaldehyde type, phenol aralkyl type, dicyclopentadiene type), polyamide, polyetheramine. The pigment is carbon black. Further, the additive A includes one or more of a dispersant (modified polyurethane, modified polyacrylate, amide polymer), a toughening agent (nitrile rubber, carboxyl-containing nitrile rubber, polyurethane, polyacrylate, etc.), a thickener (fumed silica, cellulose, polyacrylate, associative polyurethane), an adhesion promoter (organosilicon, acrylic, fluorocarbon compounds), and a coupling agent (γ-glycidyl ether propyl trimethoxy silane, γ-mercaptopropyl trimethoxy silane, γ-aminopropyl triethoxy silane, etc.).
[0012] The second insulating layer is a polyurethane resin, which is obtained by chemical reaction of a hydroxyl-containing prepolymer, an isocyanate curing agent, a pigment, and an additive B; wherein the pigment is carbon black, and in parts by mass, the hydroxyl-containing prepolymer is 45-80 parts, the isocyanate curing agent is 2-15 parts, the pigment is 5-15 parts, and the additive B is 5-15 parts. The second insulating layer is black and has a thickness of 3-10 μm. Further, the hydroxyl-containing prepolymer includes a mixture of a polyester resin and a polyether polyol, or one or two of a linear polyurethane resin, wherein the polyester resin can be selected from VYLON 226, VYLON 885, VYLON GK-810 of Toyobo, Japan; the polyether polyol can be selected from VOANOL 4240, VOANOL CP4701, VOANOL CP6001 of Dow Chemical, etc.; the linear polyurethane resin can be selected from VYLON UR4410 of Toyobo, Japan.
[0013] The hydroxyl content of the hydroxyl-containing prepolymer is 10-90 mgKOH / g; the isocyanate curing agent includes diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), hexamethylene diisocyanate, oligomers of the above three isocyanates, and end-capped modified compounds of the above three isocyanates or end-capped modified compounds of oligomers thereof, or a combination of one or more thereof. Further, the additive B includes one or more of a dispersant (modified polyurethane, modified polyacrylate, amide polymer), a thickener (fumed silica, cellulose, polyacrylate, associative polyurethane), an adhesion promoter (organic silicon, acrylic acid, fluorocarbon compounds), and a coupling agent (γ-glycidyl ether propyl trimethoxy silane, γ-mercaptopropyl trimethoxy silane, γ-aminopropyl triethoxy silane, etc.).
[0014] Furthermore, the adhesive layer is selected from one of polyurethane resin or acrylic resin without conductive powder, epoxy resin containing conductive powder, polyurethane resin containing conductive powder, and acrylic resin containing conductive powder.
[0015] Furthermore, the polyurethane resin in the adhesive layer is a carboxyl-containing thermoplastic polyurethane resin, and the acrylic resin is a carboxyl-containing thermoplastic acrylic resin. The carboxyl content of the carboxyl-containing thermoplastic polyurethane resin is 5-100 mgKOH / g. The carboxyl-containing thermoplastic polyurethane resin also includes an epoxy resin curing agent, and the carboxyl-containing thermoplastic polyurethane resin can be synthesized from a carboxyl-containing polyhydroxy compound, a polymer prepolymer containing two or more hydroxyl groups, an isocyanate, and an amine crosslinking agent. The carboxyl-containing thermoplastic polyurethane resin can be selected from VYLON UR3500 of Toyobo of Japan; the epoxy resin curing agent is one or a mixture of bisphenol A epoxy resin, bisphenol F epoxy resin, phenolic epoxy resin, bisphenol S epoxy resin, hydantoin epoxy resin, bisphenol fluorene epoxy resin, biphenyl epoxy resin and alicyclic epoxy resin, and the ratio of the carboxyl-containing thermoplastic polyurethane resin to the epoxy resin curing agent is 60:40-95:5.
[0016] Further, the epoxy resin containing conductive powder is obtained by chemical reaction of epoxy resin, curing agent, toughening agent, silane coupling agent, conductive powder and filler. The epoxy resin includes one or a mixture of bisphenol A epoxy resin, bisphenol F epoxy resin, phenolic epoxy resin, bisphenol S epoxy resin, hydantoin epoxy resin, bisphenol fluorene epoxy resin, biphenyl epoxy resin and alicyclic epoxy resin. The curing agent includes one or a mixture of aromatic amine (p-diaminodiphenyl sulfone, p-diaminodiphenylmethane, m-phenylenediamine), alicyclic amine (isophorone diamine, 1,2-cyclohexanediamine, hydrogenated p-diaminodiphenylmethane), phenolic aldehyde (phenol type, o-cresol formaldehyde type, bisphenol A formaldehyde type, phenol aralkyl type, dicyclopentadiene type), polyamide and polyetheramine. The toughening agent includes one or a combination of nitrile rubber, carboxyl-containing nitrile rubber, polyurethane, acrylate, polyimide, and phenoxy resin. The silane coupling agent is one or a combination of γ-aminopropyltriethoxysilane, γ-(2,3-propylene oxide)propyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, and γ-mercaptopropyltrimethoxysilane.
[0017] The conductive powder includes one or more of flaky copper powder, flaky silver-coated copper powder, dendritic copper powder, dendritic silver-coated copper powder, spherical copper powder, spherical silver-coated copper powder, flaky nickel powder, and beaded nickel powder. The filler is one or more of silicon dioxide, calcium carbonate, polymer microspheres insoluble in butanone, glass powder, etc.
[0018] In the present invention, the release force of the PET release film or the micro-adhesive film adhesive layer is 5-50 gf / in.
[0019] The present invention also claims a method for preparing a bendable electromagnetic shielding film, comprising the following steps:
[0020] (1) preparing a release carrier film, a metal foil, and a release protective film, preparing raw materials for a first insulating layer and a second insulating layer according to a formula, and diluting them respectively with a solvent;
[0021] (2) coating the diluted first insulating layer raw material on a release carrier film, heating to volatilize the solvent, and then aging;
[0022] (3) coating the diluted second insulating layer raw material on the surface of the cured first insulating layer, heating to evaporate the solvent, and laminating the metal foil on the surface of the second insulating layer after the solvent evaporates, followed by curing;
[0023] (4) performing surface treatment on the pressed metal foil;
[0024] (5) Applying adhesive to the treated surface of the metal foil or the surface of the release protective film, heating to volatilize the solvent in the adhesive, pressing the release protective film to the surface of the metal foil, and rolling it up.
[0025] Furthermore, the preparation method is:
[0026] (1) preparing a release carrier film, a copper foil, and a release protective film; preparing a first insulating layer, a second insulating layer, and an adhesive layer according to a formula table and diluting them with a solvent to form a coatable glue, wherein the solvent includes but is not limited to one or a combination of ethyl acetate, butanone, toluene, dimethylformamide, and acetone.
[0027] (2) coating the first insulating layer on the release carrier film, and drying in an oven to evaporate the solvent, the oven temperature is 40°C-160°C, and the coating line speed is 3m / min-100m / min; after baking, the film is rolled up and placed in the oven for curing for a period of time; the curing temperature is between 50°C-120°C, and the curing time is between 12hr-200hr; if necessary, curing is performed continuously at multiple temperatures and times.
[0028] (3) Coat the second insulating layer on the surface of the cured first insulating layer, and dry in an oven to evaporate the solvent. The oven temperature is 40℃-160℃, and the coating line speed is 3m / min-30m / min. After the solvent evaporates, the copper foil can be immediately pressed on the coating production line, or it can be rolled up and pressed on a laminator; the temperature of pressing the copper foil is 20℃-100℃, and the pressing pressure is 0.2MPa-1MPa. After pressing the copper foil, roll it up and place it in an oven for a period of time; the curing temperature is between 50℃-120℃, and the curing time is between 12hr-200hr; if necessary, continue to cure at multiple temperatures and times.
[0029] (4) The laminated copper foil is subjected to surface treatment, and the treatment method includes one of redding treatment, browning treatment, and blackening treatment.
[0030] (5) Apply adhesive to the treated copper foil surface or release protective film surface. Dry in an oven to evaporate the solvent. The oven temperature is 40℃-160℃ and the coating line speed is 3m / min-100m / min. After the solvent evaporates, press the release protective film directly onto the metal foil surface and roll it up. Pressing conditions: temperature is 20℃-100℃ and pressing pressure is 0.2MPa-1MPa.
[0031] Compared with the prior art, the electromagnetic shielding film obtained by the present invention has the following advantages:
[0032] 1. The electromagnetic shielding film obtained by this technology has extremely high shielding effectiveness and can be used in 5G communication electronic equipment. The product can withstand soldering at 288°C for 10s×3 times and can be bent a certain number of times.
[0033] 2. The design of double-layer insulation layer, the first insulation layer uses epoxy resin, which has a high cross-linking density, can withstand solvent wiping (methyl ethyl ketone, ethanol, toluene, plate cleaning liquid, etc.), and is not easy to flow during lamination (180℃, 10MPa, 2min), so it can withstand high step difference (step difference refers to the surface height difference caused by the wiring design of the FPC board). The second insulation layer uses polyurethane resin and acrylate resin as the main resin, which has high flexibility. On the one hand, it plays the role of bonding the copper foil and the first insulation layer. On the other hand, when the electromagnetic shielding film is bent, it will not break, which can prevent the copper foil from leaking.
[0034] 3. Before applying the adhesive, the laminated copper foil is surface treated, which can effectively improve the problem of reflow soldering explosion. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 :Schematic diagram of electromagnetic shielding film structure
[0036] Among them, 1 is a release carrier film; 2 is an insulating layer; 21 is a first insulating layer; 22 is a second insulating layer; 3 is a copper foil shielding layer; 4 is an adhesive layer; and 5 is a release protective film. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is described in detail below through specific embodiments.
[0038] Example 1
[0039] An electromagnetic shielding film with high electromagnetic shielding effectiveness and bendable for use is prepared, and the preparation method thereof comprises the following steps:
[0040] (1) Prepare a release carrier film 1, a copper foil 3, and a release protective film 5; prepare the first insulating layer 21, the second insulating layer 22, and the adhesive layer 4 according to the formula and dilute them with a solvent to form a coatable glue. The release carrier film 1 is a polyethylene terephthalate (PET) matte release film with a thickness of 50 μm; the copper foil 3 is a rolled copper foil with a thickness of 6 μm; and the release protective film 5 is a PET release film with a thickness of 60 μm. The raw material formula of the first insulating layer 21 is: by mass, 55 parts of bisphenol A epoxy resin prepolymer, 25 parts of para-diaminodiphenyl sulfone, 10 parts of carbon black, and 20 parts of additive A (4 parts of dispersant, 4 parts of toughening agent, 4 parts of thickener, 4 parts of adhesion promoter, and 4 parts of coupling agent).
[0041] The raw material formula of the second insulating layer 22 is: 60 parts of hydroxyl-containing prepolymer, 10 parts of diphenylmethane diisocyanate, 10 parts of carbon black, and 10 parts of additive B. The hydroxyl-containing prepolymer is a hydroxyl-containing prepolymer including 30 parts of polyester resin and 30 parts of polyether polyol, and the additive B includes 3 parts of dispersant, 3 parts of thickener, 2 parts of adhesion promoter, and 2 parts of coupling agent by mass.
[0042] The raw materials of the adhesive layer 4 include: polyurethane resin without conductive powder, specifically 85 parts of carboxyl-containing thermoplastic polyurethane resin and 15 parts of bisphenol F epoxy resin.
[0043] The first insulating layer 21, the second insulating layer 22 and the adhesive layer 4 are made of the same solvent, which is a mixture of toluene and butanone, with a volume ratio of toluene:butanone=1:1.
[0044] (2) Coating the first insulating layer 21 on the release carrier film 1 with a coating thickness of 8 μm, and drying in an oven to evaporate the solvent. The oven temperature is 80° C. and the coating line speed is 90 m / min. After baking, the film is rolled up and placed in an oven for a period of time. The curing temperature is 90° C. and the curing time is 80 h.
[0045] (3) The second insulating layer 22 is coated on the surface of the cured first insulating layer 21, with a coating thickness of 12 μm, and the solvent is evaporated by oven drying. The oven temperature is 80°C and the coating line speed is 20 m / min. After the solvent evaporates, the copper foil 3 can be immediately pressed on the coating production line; the temperature of pressing the copper foil 3 is 70°C and the pressing pressure is 0.2 MPa-1 MPa. After pressing the copper foil 3, it is rolled up and placed in an oven for a period of time; the curing temperature is between 90°C and the curing time is 80 hours.
[0046] (4) The pressed copper foil 3 is subjected to surface treatment by browning.
[0047] (5) Apply adhesive to the treated copper foil 3. The coating thickness is 18 μm. The solvent is evaporated by oven drying. The oven temperature is 80°C and the coating line speed is 90 m / min. After the solvent evaporates, the release protective film 5 is directly pressed and rolled up. The conditions for pressing the release protective film 5 are: the temperature is 80°C and the pressing pressure is 0.2 MPa-1 MPa.
[0048] The obtained product is recorded as S1. In the final product S1, the release carrier film 1 has a thickness of 50 μm, the first insulating layer 21 has a thickness of 3 μm, the second insulating layer 22 has a thickness of 8 μm, the copper foil 3 has a thickness of 6 μm, the adhesive layer 4 has a thickness of 13 μm, and the PET release film 5 has a thickness of 60 μm.
[0049] Example 2
[0050] An electromagnetic shielding film with high electromagnetic shielding effectiveness and bendable for use is prepared, and the preparation method thereof comprises the following steps:
[0051] (1) Prepare a release carrier film 1, a copper foil 3, and a release protective film 5; prepare the first insulating layer 21, the second insulating layer 22, and the adhesive layer 4 according to the formula and dilute them with a solvent to form a coatable glue. The release carrier film 1 is a PET release film with a thickness of 50 μm; the copper foil 3 is a rolled copper foil with a thickness of 6 μm; and the release protective film 5 is a PET micro-adhesive film with a thickness of 60 μm. The raw material formula of the first insulating layer 21 is: by weight, 20 parts of bisphenol F epoxy resin prepolymer, 40 parts of m-phenylenediamine, 10 parts of carbon black, and 30 parts of additive A; wherein the additive A, by weight, includes 6 parts of dispersant, 6 parts of toughening agent, 6 parts of thickener, 6 parts of adhesion promoter, and 6 parts of coupling agent.
[0052] The raw material formula of the second insulating layer 22 is: 60 parts of linear polyurethane, 10 parts of diphenylmethane diisocyanate, 10 parts of carbon black, and 10 parts of additive B. Additive B includes 3 parts of dispersant, 3 parts of thickener, 2 parts of adhesion promoter, and 2 parts of coupling agent by mass.
[0053] The raw materials of the adhesive layer 4 include: polyurethane resin without conductive powder, specifically 85 parts of carboxyl-containing thermoplastic polyurethane resin and 15 parts of bisphenol F epoxy resin.
[0054] The first insulating layer 21, the second insulating layer 22 and the adhesive layer 4 are made of the same solvent, which is dimethylformamide.
[0055] (2) Coating the first insulating layer 21 on the release carrier film 1 with a coating thickness of 8 μm, and drying in an oven to evaporate the solvent. The oven temperature is 50° C. and the coating line speed is 60 m / min. After baking, the film is rolled up and placed in an oven for a period of time. The curing temperature is 60° C. and the curing time is 120 h.
[0056] (3) The second insulating layer 22 is coated on the surface of the cured first insulating layer 21, with a coating thickness of 12 μm, and the solvent is evaporated by oven drying. The oven temperature is 50°C and the coating line speed is 5 m / min. After the solvent evaporates, the copper foil 3 can be immediately pressed on the coating production line; the temperature of pressing the copper foil 3 is 40°C and the pressing pressure is 0.2 MPa-1 MPa. After pressing the copper foil 3, it is rolled up and placed in an oven for a period of time; the curing temperature is between 60°C and the curing time is 130 hours.
[0057] (4) The pressed copper foil 3 is subjected to surface treatment, and the treatment method is reddening treatment.
[0058] (5) Apply adhesive to the treated copper foil 3. The coating thickness is 18 μm. The solvent is evaporated by oven drying. The oven temperature is 50° C. and the coating line speed is 20 m / min. After the solvent evaporates, the release protective film 5 is directly pressed and rolled up. The conditions for pressing the release protective film 5 are: the temperature is 30° C. and the pressing pressure is 0.2 MPa-1 MPa.
[0059] The obtained product is recorded as S2. In the final product S2, the release carrier film 1 has a thickness of 50 μm, the first insulating layer 21 has a thickness of 3 μm, the second insulating layer 22 has a thickness of 8 μm, the copper foil 3 has a thickness of 6 μm, the adhesive layer 4 has a thickness of 13 μm, and the PET release film 5 has a thickness of 60 μm.
[0060] Example 3
[0061] An electromagnetic shielding film with high electromagnetic shielding effectiveness and bendable for use is prepared, and the preparation method thereof comprises the following steps:
[0062] (1) Prepare a release carrier film 1, a copper foil 3, and a release protective film 5; the first insulating layer 21, the second insulating layer 22, and the adhesive layer 4 are formulated according to the formula and diluted with a solvent to form a coatable glue. The release carrier film 1 is a polyethylene terephthalate (PET) matte release film with a thickness of 50 μm; the copper foil 3 is a rolled copper foil with a thickness of 6 μm; and the release protective film 5 is a PET release film with a thickness of 60 μm. The raw material formula of the first insulating layer 21 is: by weight, 55 parts of biphenyl epoxy resin prepolymer, 15 parts of p-diaminodiphenyl sulfone + 10 parts of metaphenylenediamine, 10 parts of carbon black, and 20 parts of additive A; wherein the additive A, by weight, includes 4 parts of dispersant, 4 parts of toughening agent, 4 parts of thickener, 4 parts of adhesion promoter, and 4 parts of coupling agent.
[0063] The raw material formula of the second insulating layer 22 is: 40 parts of hydroxyl-containing prepolymer, 18 parts of hexamethylene diisocyanate, 10 parts of carbon black, and 20 parts of additive B. The hydroxyl-containing prepolymer is linear polyurethane, and the additive B includes 5 parts of dispersant, 5 parts of thickener, 5 parts of adhesion promoter, and 5 parts of coupling agent by mass.
[0064] The raw materials of the adhesive layer 4 include: polyurethane resin without conductive powder, specifically 85 parts of carboxyl-containing thermoplastic polyurethane resin and 15 parts of bisphenol A epoxy resin.
[0065] The first insulating layer 21, the second insulating layer 22 and the adhesive layer 4 are made of the same solvent, which is a mixture of toluene and butanone, with a volume ratio of toluene:butanone=1:1.
[0066] (2) Coating the first insulating layer 21 on the release carrier film 1 with a coating thickness of 8 μm, and drying in an oven to evaporate the solvent. The oven temperature is 120° C. and the coating line speed is 20 m / min. After baking, the film is rolled up and placed in an oven for a period of time. The curing temperature is 120° C. and the curing time is 20 h.
[0067] (3) The second insulating layer 22 is coated on the surface of the cured first insulating layer 21, with a coating thickness of 12 μm, and the solvent is evaporated by oven drying. The oven temperature is 120°C and the coating line speed is 30 m / min. After the solvent evaporates, the copper foil 3 can be immediately pressed on the coating production line; the temperature for pressing the copper foil 3 is 100°C and the pressing pressure is 0.2 MPa-1 MPa. After pressing the copper foil 3, it is rolled up and placed in an oven for a period of time; the curing temperature is between 120°C and the curing time is 20 hours.
[0068] (4) The laminated copper foil 3 is subjected to surface treatment, wherein the treatment method is blackening treatment.
[0069] (5) Apply adhesive to the treated copper foil 3. The coating thickness is 18 μm. The solvent is evaporated by oven drying. The oven temperature is 150° C. and the coating line speed is 10 m / min. After the solvent evaporates, the release protective film 5 is directly pressed and rolled up. The conditions for pressing the release protective film 5 are: the temperature is 100° C. and the pressing pressure is 0.2 MPa-1 MPa.
[0070] The obtained product is recorded as S3. In the final product S3, the release carrier film 1 has a thickness of 50 μm, the first insulating layer 21 has a thickness of 3 μm, the second insulating layer 22 has a thickness of 8 μm, the copper foil 3 has a thickness of 6 μm, the adhesive layer 4 has a thickness of 13 μm, and the PET release film 5 has a thickness of 60 μm.
[0071] Example 4
[0072] An electromagnetic shielding film with high electromagnetic shielding effectiveness and bendable for use is prepared, and the preparation method thereof comprises the following steps:
[0073] (1) Prepare a release carrier film 1, a copper foil 3, and a release protective film 5; the first insulating layer 21, the second insulating layer 22, and the adhesive layer 4 are formulated according to the formula and diluted with a solvent to form a coatable glue. The release carrier film 1 is a polyethylene terephthalate (PET) matte release film with a thickness of 50 μm; the copper foil 3 is a rolled copper foil with a thickness of 6 μm; and the release protective film 5 is a PET release film with a thickness of 60 μm. The raw material formula of the first insulating layer 21 is: by mass, 20 parts of bisphenol F epoxy resin prepolymer, 20 parts of m-phenylenediamine + 20 parts of hydrogenated p-diaminodiphenylmethane, 10 parts of carbon black, and 30 parts of additive A. Additive A includes 6 parts of dispersant, 6 parts of toughening agent, 6 parts of thickener, 6 parts of adhesion promoter, and 6 parts of coupling agent.
[0074] The raw material formula of the second insulating layer 22 is: 40 parts of linear polyurethane, 18 parts of toluene diisocyanate, 10 parts of carbon black, and 25 parts of additive B. Additive B includes 8 parts of dispersant, 9 parts of thickener, 5 parts of adhesion promoter, and 3 parts of coupling agent.
[0075] The raw materials of the adhesive layer 4 include: polyurethane resin without conductive powder, specifically 85 parts of carboxyl-containing thermoplastic polyurethane resin and 15 parts of bisphenol F epoxy resin.
[0076] The first insulating layer 21, the second insulating layer 22 and the adhesive layer 4 are made of the same solvent, which is a mixture of toluene and butanone, with a volume ratio of toluene:butanone=1:1.
[0077] (2) Coating the first insulating layer 21 on the release carrier film 1 with a coating thickness of 8 μm, and drying in an oven to evaporate the solvent. The oven temperature is 80° C. and the coating line speed is 90 m / min. After baking, the film is rolled up and placed in an oven for a period of time. The curing temperature is 90° C. and the curing time is 80 h.
[0078] (3) The second insulating layer 22 is coated on the surface of the cured first insulating layer 21, with a coating thickness of 12 μm, and the solvent is evaporated by oven drying. The oven temperature is 80°C and the coating line speed is 20 m / min. After the solvent evaporates, the copper foil 3 can be immediately pressed on the coating production line; the temperature of pressing the copper foil 3 is 70°C and the pressing pressure is 0.2 MPa-1 MPa. After pressing the copper foil 3, it is rolled up and placed in an oven for a period of time; the curing temperature is between 90°C and the curing time is 80 hours.
[0079] (4) The pressed copper foil 3 is subjected to surface treatment by browning.
[0080] (5) Apply adhesive to the treated copper foil 3. The coating thickness is 18 μm. The solvent is evaporated by oven drying. The oven temperature is 80°C and the coating line speed is 90 m / min. After the solvent evaporates, the release protective film 5 is directly pressed and rolled up. The conditions for pressing the release protective film 5 are: the temperature is 80°C and the pressing pressure is 0.2 MPa-1 MPa.
[0081] The obtained product is recorded as S4. In the final product S1, the release carrier film 1 has a thickness of 50 μm, the first insulating layer 21 has a thickness of 3 μm, the second insulating layer 22 has a thickness of 8 μm, the copper foil 3 has a thickness of 6 μm, the adhesive layer 4 has a thickness of 13 μm, and the PET release film 5 has a thickness of 60 μm.
[0082] Example 5
[0083] An electromagnetic shielding film with high electromagnetic shielding effectiveness and bendable for use is prepared, and the preparation method thereof comprises the following steps:
[0084] (1) Prepare a release carrier film 1, a copper foil 3, and a release protective film 5; prepare the first insulating layer 21, the second insulating layer 22, and the adhesive layer 4 according to the formula and dilute them with a solvent to form a coatable glue. The release carrier film 1 is a polyethylene terephthalate (PET) matte release film with a thickness of 50 μm; the copper foil 3 is a rolled copper foil with a thickness of 6 μm; and the release protective film 5 is a PET release film with a thickness of 60 μm. The raw material formula of the first insulating layer 21 is: by weight, 55 parts of bisphenol A epoxy resin prepolymer, 25 parts of para-diaminodiphenyl sulfone, 10 parts of carbon black, and 20 parts of additive A; wherein the additive A, by weight, includes 4 parts of dispersant, 4 parts of toughening agent, 4 parts of thickener, 4 parts of adhesion promoter, and 4 parts of coupling agent.
[0085] The raw material formula of the second insulating layer 22 is: 60 parts of hydroxyl-containing prepolymer, 10 parts of diphenylmethane diisocyanate, 10 parts of carbon black, and 10 parts of additive B. The hydroxyl-containing prepolymer is linear polyurethane, and the additive B includes 3 parts of dispersant, 3 parts of thickener, 2 parts of adhesion promoter, and 2 parts of coupling agent by mass.
[0086] The raw materials of the adhesive layer 4 include: epoxy resin containing conductive powder, specifically 18 parts of phenolic epoxy resin, 38 parts of p-diaminodiphenylmethane, 30 parts of polyimide, 5 parts of flaky copper powder, 7 parts of spherical copper powder, 3 parts of γ-aminopropyltriethoxysilane, and 2 parts of γ-mercaptopropyltrimethoxysilane.
[0087] The first insulating layer 21, the second insulating layer 22 and the adhesive layer 4 are made of the same solvent, which is a mixture of toluene and butanone, with a volume ratio of toluene:butanone=1:1.
[0088] (2) Coating the first insulating layer 21 on the release carrier film 1 with a coating thickness of 8 μm, and drying in an oven to evaporate the solvent. The oven temperature is 80° C. and the coating line speed is 90 m / min. After baking, the film is rolled up and placed in an oven for a period of time. The curing temperature is 90° C. and the curing time is 80 h.
[0089] (3) The second insulating layer 22 is coated on the surface of the cured first insulating layer 21, with a coating thickness of 12 μm, and the solvent is evaporated by oven drying. The oven temperature is 80°C and the coating line speed is 20 m / min. After the solvent evaporates, the copper foil 3 can be immediately pressed on the coating production line; the temperature of pressing the copper foil 3 is 70°C and the pressing pressure is 0.2 MPa-1 MPa. After pressing the copper foil 3, it is rolled up and placed in an oven for a period of time; the curing temperature is between 90°C and the curing time is 80 hours.
[0090] (4) The laminated copper foil 3 is subjected to surface treatment, wherein the treatment method is blackening treatment.
[0091] (5) Apply adhesive to the treated copper foil 3. The coating thickness is 18 μm. The solvent is evaporated by oven drying. The oven temperature is 80°C and the coating line speed is 90 m / min. After the solvent evaporates, the release protective film 5 is directly pressed and rolled up. The conditions for pressing the release protective film 5 are: the temperature is 80°C and the pressing pressure is 0.2 MPa-1 MPa.
[0092] The obtained product is recorded as S5. In the final product S5, the release carrier film 1 has a thickness of 50 μm, the first insulating layer 21 has a thickness of 3 μm, the second insulating layer 22 has a thickness of 8 μm, the copper foil 3 has a thickness of 6 μm, the adhesive layer 4 has a thickness of 13 μm, and the PET release film 5 has a thickness of 60 μm.
[0093] In order to verify the excellent performance of the electromagnetic shielding film obtained by the present invention, the following comparative example was set up.
[0094] Comparative Example 1
[0095] The difference from Example 1 is that there is no first insulating layer. The product is recorded as B1.
[0096] Comparative Example 2
[0097] The difference from Example 1 is that the copper foil 3 after lamination is not subjected to any surface treatment. The product is recorded as B2.
[0098] Comparative Example 3
[0099] The difference from Example 1 is that there is no second insulating layer. The product is recorded as B3.
[0100] Comparative Example 4
[0101] The difference from Example 1 is that copper foil is not used, but copper plating is used as the shielding layer. The product is recorded as B4.
[0102] In the above embodiments and comparative examples, the treatment methods for the copper foil 3 include red treatment, brown treatment, and black treatment, wherein the red treatment is copper plating on the copper surface. Both browning and blackening are micro-etching on the surface of the copper foil and generating copper oxide to increase the bonding force between the surface of the copper foil 3 and the resin. The difference is that blackening is an oxidation reaction in an alkaline medium, mainly generating copper oxide, and browning is in an acidic medium, mainly generating cuprous oxide. These three treatment methods are all conventional treatment methods in the industry.
[0103] Table 1 Main raw material types, dosages and surface treatment methods of copper foil in the examples
[0104]
[0105]
[0106]
[0107] The electromagnetic shielding films obtained in the above embodiments and comparative examples were tested for their performance:
[0108] 1. Reference standard ASTM 4935. Test frequency range: 1GHz~10GHz.
[0109] 2. Bending performance: Refer to the standard IPC-TM-650. Cut the shielding film sample into a test sample with a length of 15 cm and a width of 1 cm and press it (180°C, 100Kgf / cm 2 , 2min) to the surface of the flexible circuit board. After the sample is aged for 1 hour, it is placed on the MIT folding tester for testing. The shielding film folding times are recorded based on the standard that the shielding layer (ultra-thin copper foil) is not exposed.
[0110] 3. Solvent resistance: Cut the shielding film sample into 5cm×5cm test samples and press them together (180℃, 100Kgf / cm 2 , 2min) to the surface of the flexible circuit board. After the sample matures for 1 hour, use a 1mm spacing hundred-grid knife to cut a 10-grid × 10-grid pattern, and soak it in butanone for 10 minutes. After soaking, the sample is cleaned with deionized water and wiped with a dust-free cloth. Then use 3M600 tape to test the adhesion of the sample and observe whether there is delamination and bulging on the surface of the shielding film.
[0111] 4. Step performance test: Take polyimide reinforcement plate samples of different thicknesses, cut them into strips of 1cm long × 1cm wide, press them (180℃, 100Kgf / cm 2 , 2min) to the surface of the flexible circuit board. Then take the shielding film sample, cut it into a size of 4cm long × 1cm wide, and press it vertically with the reinforcing plate (180℃, 100Kgf / cm 2 , 2min). After the quick pressing is completed, the PET release film is torn off and the sample is placed under a microscope to observe whether the shielding film has copper leakage. The thickness of the reinforcement plate is 50μm, 75μm, 100μm, 125μm, 150μm, 200μm, 250μm, and 300μm for testing. The maximum reinforcement plate thickness without copper leakage is used as the step resistance data of the shielding film.
[0112] 5. Reflow soldering resistance: Referring to the standard IPC-TM-650 2.4.13, the shielding film samples were cut into 3cm×3cm test samples and pressed (180℃, 100Kgf / cm 2After the sample is aged for 1 hour, it is placed in a 288°C tin furnace for 10 seconds to observe whether the shielding film surface is bulging.
[0113] The above performance test results are shown in Table 2 below.
[0114] Table 2 Performance test results of electromagnetic shielding film products in the embodiments and comparative examples
[0115]
[0116] Figure 1 The structure of the electromagnetic shielding film of the present invention is given, including a release carrier film 1, a first insulating layer 21 coated on the release carrier film 1, a second insulating layer 22 coated on the first insulating layer 21, a metal foil shielding layer 3 bonded to the second insulating layer 22, an adhesive layer 4 arranged on the metal foil shielding layer 3 and a release protective film 5 bonded to the adhesive layer 4.
[0117] It can be seen from Table 2 above that the electromagnetic shielding film obtained by adopting the technical solution of the present invention has good performances and is better than the electromagnetic shielding film obtained in the comparative example.
[0118] In the present invention, the performance of the first and second insulating layers is related to the thickness of each layer: the thicker the first insulating layer 21, the better the solvent resistance; the thicker the second insulating layer 22, the better the bending performance. In addition, too much thickness of the copper foil 3 will greatly reduce the bending performance of the electromagnetic shielding film. Therefore, in order to avoid the influence of thickness on the performance of the electromagnetic shielding film in the present invention, the thickness of each layer in the embodiment and the comparative example is designed to be the same, so as to study the influence of the raw material formula of each layer on the performance of the electromagnetic shielding film.
[0119] For product S1, the electromagnetic shielding film obtained by using the preferred raw material ratio of the first insulating layer 21 and the second insulating layer 22 of the present invention and combining the electromagnetic shielding film preparation method of the present invention has the best performance. The first or second insulating layer formula of products S2-S5, or the addition of conductive powder to the adhesive layer 4, therefore, the comprehensive performance of products S2-S5 is worse than that of S1.
[0120] Comparative Example Products B1, B2 and B3, compared with Example Products S1-S5, have different raw materials for the first insulating layer 21 and the second insulating layer 22, or the copper foil 3 is not surface treated after lamination, so the comprehensive performance of B1, B2 and B3 is worse than S1-S5. Comparative Example Product B4, compared with Example Product S1, uses copper plating as the shielding layer, and the shielding effectiveness is significantly reduced, and the shielding effectiveness is significantly lower than all the products in other Examples and Comparative Examples, which shows that copper foil can give the electromagnetic shielding film a higher shielding effectiveness.
[0121] Surface treatment of the copper foil 3 will reduce the thickness of the copper foil, thereby improving the bending performance, and at the same time improving the reflow soldering resistance of the electromagnetic shielding film. The bending performance is also related to the adhesive layer 4. The adhesive layer containing conductive powder in the formula has a high hardness, so the bending performance is poor. In this product, the first insulating layer 21 is mainly resistant to solvent wiping, has good step performance, and slightly poor bending performance; the second insulating layer 22 is mainly good in bending performance, but poor in solvent resistance.
[0122] Although the present invention has been described with reference to preferred embodiments, various modifications may be made thereto without departing from the scope of the present invention. In particular, the various technical features mentioned in the various embodiments may be combined in any manner as long as there is no conflict. The present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A bendable electromagnetic shielding film, characterized in that: The bendable electromagnetic shielding film comprises a release carrier film, a first insulating layer coated on the release carrier film, a second insulating layer coated on the first insulating layer, a metal foil shielding layer attached to the second insulating layer, an adhesive layer provided on the metal foil shielding layer, and a release protective film attached to the adhesive layer; The first insulating layer is epoxy resin, and the epoxy resin is obtained by chemical reaction of epoxy resin prepolymer, curing agent, pigment and additive A; The second insulating layer is a polyurethane resin, which is obtained by chemical reaction of a hydroxyl-containing prepolymer, an isocyanate curing agent, a pigment, and an additive B; The adhesive layer is selected from one of polyurethane resin without conductive powder, acrylic resin without conductive powder, epoxy resin with conductive powder, polyurethane resin with conductive powder, and acrylic resin with conductive powder; The method for preparing the electromagnetic shielding film comprises the following steps: (1) preparing a release carrier film, a metal foil, and a release protective film, preparing raw materials for a first insulating layer, a second insulating layer, and an adhesive layer according to a formula, and diluting them with a solvent respectively; (2) coating the diluted first insulating layer raw material on a release carrier film, heating to volatilize the solvent, and then aging; (3) coating the diluted second insulating layer raw material on the surface of the cured first insulating layer, heating to evaporate the solvent, and laminating the metal foil on the surface of the second insulating layer after the solvent evaporates, followed by curing; (4) performing surface treatment on the pressed metal foil; the surface treatment is one of reddening treatment, browning treatment and blackening treatment; (5) Applying adhesive to the treated surface of the metal foil or the surface of the release protective film, heating to volatilize the solvent in the adhesive, pressing the release protective film to the surface of the metal foil, and rolling it up.
2. The bendable electromagnetic shielding film according to claim 1, characterized in that: In parts by mass, the contents of the raw materials in the first insulating layer are: 30-65 parts of epoxy resin prepolymer, 15-35 parts of curing agent, 5-15 parts of pigment, and 5-25 parts of additive A.
3. The bendable electromagnetic shielding film according to claim 2, characterized in that: Calculated by weight, the contents of the raw materials in the second insulating layer are: 45-80 parts of hydroxyl-containing prepolymer, 2-15 parts of isocyanate curing agent, 5-15 parts of carbon black, and 5-15 parts of additive B.
4. The bendable electromagnetic shielding film according to claim 3, characterized in that: Additive A includes one or more of a dispersant, a toughening agent, a thickener, an adhesion promoter, and a coupling agent; Additive B includes one or more of a dispersant, a thickener, an adhesion promoter, and a coupling agent.
5. The bendable electromagnetic shielding film according to claim 1, characterized in that: In the adhesive layer, the polyurethane resin is a carboxyl-containing thermoplastic polyurethane resin, and the acrylic resin is a carboxyl-containing thermoplastic acrylic resin.
6. The bendable electromagnetic shielding film according to claim 1, characterized in that: The epoxy resin containing conductive powder is obtained by chemical reaction of epoxy resin, curing agent, toughening agent, silane coupling agent, conductive powder and filler.
Citation Information
Patent Citations
Ultrathin shielding film with high shielding efficiency and production method thereof
CN102711428A
Electromagnetic shielding membrane with excellent shielding performance and production technology thereof
CN104853576A
Electromagnetic shielding film
CN106003916A
Double-layer electromagnetic shielding film and preparation method thereof
CN109130383A
Electromagnetic shielding film capable of being bent for use
CN211152613U